Three-Terminal Amorphous Silicon Solar Cells - Cheng-Hung Tai; Chu-Hsuan Lin; Chih-Ming Wang; Chun-Chieh Lin (International Journal of Photoenergy)
Many defects exist within amorphous silicon since it is not crystalline. This provides recombination centers, thus reducing the efficiency of a typical a-Si solar cell. A new structure is presented in this paper: a three-terminal a-Si solar cell. The new back-to-back p-i-n/n-i-p structure increased the average electric field in a solar cell. A typical a-Si p-i-n solar cell was also simulated for comparison using the same thickness and material parameters. The 0.28 μm-thick three-terminal a-Si solar cell achieved an efficiency of 11.4%, while the efficiency of a typical a-Si p-i-n solar cell was 9.0%. Furthermore, an efficiency of 11.7% was achieved by thickness optimization of the three-terminal solar cell.